Survival Benefit of Three Different Therapies in Postoperative Patients With Advanced Gastric Cancer: A Network Meta-Analysis - Wu, Dong-Mei; Wang, Shan; Wen, Xin; Han, Xin-Rui; Wang, Yong-Jian; Shen, Min; Fan, Shao-Hua; Zhang, Zi-Feng; Zhuang, Juan; Shan, Qun; Li, Meng-Qiu; Hu, Bin; et al. (Frontiers in Pharmacology, 2018)
Purpose: Gastric cancer is mainly treated by gastrectomy, the results of which were unsatisfactory without any adjuvant treatments. This study aimed to examine the performance of radiotherapy, chemotherapy, and chemoradiotherapy after surgery in order to acquire the optimum treatment. Method: Embase and PubMed were retrieved to conduct a systematic research. Hazard ratios (HR) of overall survival (OS) and progression-free survival (PFS) were calculated by synthesizing direct and indirect evidence to evaluate the efficacy of three treatments against surgery alone. The P-score ranking was utilized to rank the therapies. Consistency was assessed by heat plot. Begg’s test was performed to evaluate publication bias. Results: A total of 35 randomized controlled studies (RCTs) with 8973 patients were included in our network meta-analysis (NMA). As for efficacy outcomes, OS and PFS of 1 year, 2 years, 3 years, and 5 years, all revealed the excellent performance of chemoradiotherapy (CRT) as the best of three adjuvant therapies. Meanwhile, P-score ranking results also displayed that CRT was the optimal regimen. Additionally, radiotherapy (RT) and chemotherapy (CT) were two alternative options following CRT since RT performed well in short-term survival while CT could improve the long-term survival. Conclusion: CRT was the most recommended therapy to accompany surgery according to our results. However, no analysis about the safety of these three treatments was mentioned in our study. Further studies including safety outcomes were required to draw a more comprehensive conclusion.